2013
DOI: 10.3389/fonc.2013.00072
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Radiation Response of Lung Cancer with Different Gene Mutations Using Genetically Engineered Mice

Abstract: Purpose: Non-small cell lung cancers (NSCLC) are a heterogeneous group of carcinomas harboring a variety of different gene mutations. We have utilized two distinct genetically engineered mouse models of human NSCLC (adenocarcinoma) to investigate how genetic factors within tumor parenchymal cells influence the in vivo tumor growth delay after one or two fractions of radiation therapy (RT).Materials and Methods: Primary lung adenocarcinomas were generated in vivo in mice by intranasal delivery of an adenovirus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…We therefore analysed spleens from DNR-treated Trp53- wt and -null mice for p21 induction. Immunoblotting showed elevated expression of p21 in spleens from wt-mice at 24 and 48 hours after DNR treatment (Figure 3, left panel) similar to what is seen with other DNA-damaging agents [22,23]. The Trp53 null mice had only modest increase in p21 levels (Figure 3, right panel).…”
Section: Resultssupporting
confidence: 53%
“…We therefore analysed spleens from DNR-treated Trp53- wt and -null mice for p21 induction. Immunoblotting showed elevated expression of p21 in spleens from wt-mice at 24 and 48 hours after DNR treatment (Figure 3, left panel) similar to what is seen with other DNA-damaging agents [22,23]. The Trp53 null mice had only modest increase in p21 levels (Figure 3, right panel).…”
Section: Resultssupporting
confidence: 53%
“…In this study, we utilized our previously tested RT regimen, which consists of 17 Gy in 2 fractions of 8.5 Gy, given on 2 consecutive days approximately 24 hours apart (8.5 Gy × 2). While the translation of radiation doses and fractionation schemes used in humans to mice is difficult and not very well studied (8,18), prior work has shown that multi-fraction RT is more effective than single-fraction RT when combined with CTLA-4 checkpoint blockade in syngeneic tumor models (19). Additionally, we used a previously described timing approach of the immunomodulatory agent and initiated αPD-1 treatment 6 hours after the second fraction of 8.5 Gy ( Figure 1A) (20).…”
Section: Resultsmentioning
confidence: 99%
“…The translation of treatment doses and fractionation schemes used in humans to mice is difficult and not very well studied (8,18). Whereas in the majority of in vivo RT studies a single dose is prescribed, Dewan and colleagues specifically analyzed the efficacy of different dose-fractionation regimens with CTLA-4 blockade in two syngeneic mouse models (breast and colorectal cancer) and showed superiority of the multi-fraction versus single-fraction approach (19).…”
Section: Discussionmentioning
confidence: 99%
“…Mice were then humanly euthanized at either a fixed time point (four months post AdCre) or upon reaching a moribundity endpoint. A subset of the latter mice were also radiologically imaged monthly using micro-computed tomography (CT) [43]. CT scans were reviewed in a blinded fashion using Image-J.…”
Section: Methodsmentioning
confidence: 99%